Improvement of efficiency of use of liquid-glass mixtures. Part 4. Combined strengthening - A. N. Krutilin; Yu. Yu. Huminski; O. A. Rusevich; L. V. Kulbitskaya (Литьë и металлургия)
Technological methods applied for intensification liquid-glass mixture hardening process are described. Influence of physical and chemical processes at liquid-glass mixtures technological properties are examined. The application of combined methods of hardening the mixture is proposed, as well as examples of such technological processes are given. The effect of combined methods on the technological properties of the mixture is described. The need for more hard research in this area is justified